Collision tumors of the thyroid: A case report and review of the literature. Issue 10 (30th June 2015) - Ryan, Neil; Walkden, Graham; Lazic, Darko; Tierney, Paul
Abstract: Background: Collision tumors of the thyroid are a rare pathology that present a diagnostic and treatment challenge. In this report, we present an interesting case and a review of the current literature as to inform management. Methods and Results: An 88‐year‐old woman presented with acute airway compromise and vocal cord paralysis. CT identified a thyroid mass and widespread metastasis. Histopathology identified the lesion as a collision tumor consisting of a squamous cell carcinoma (SCC) and papillary thyroid carcinoma. The patient was managed with surgery and palliative radiotherapy. However, she died from complications of a lower respiratory tract infection. We also present a review of the literature with 33 cases reviewed. Conclusion: Management of collision tumors is complex because of the duality of the pathology. They should be managed in a multidisciplinary team setting and treatment should be patient specific. Generally, the most aggressive neoplasm should guide treatment. We recommend surgical management with adjunct therapy. © 2015 Wiley Periodicals, Inc. Head Neck 37: E125–E129, 2015